An investigation of the NO/H2/O2 (Lean De-NOx) reaction on a highly active and selective Pt/La0.7Sr0.2Ce0.1FeO3 catalyst at low temperatures - Andronikou, Ch.; Costa, Costas; Savva, Petros G. (My University, 2002)
A 0.1 wt% Pt supported on La0.7Sr0.2Ce0.1FeO3 solid (mixed oxide containing LaFeO3, SrFeO3-x, CeO2, and Fe2O3 phases) has been studied for the NO/H2/O2 reaction in the 100-400°C range. For a critical comparison, 0.1 wt% Pt was supported on SiO2, CeO2, and Fe2O3 and tested under the same reaction conditions. For the Pt/La0.7Sr0.2Ce0.1FeO3 catalyst a maximum in the NO conversion (83%) has been observed at 150°C with a N2 selectivity value of 93%, while for the Pt/SiO2 catalyst at 120°C (82% conversion) with a N2 selectivity value of 65% using a GHSV of 80,000 h-1 Low N2 selectivity values, less than 45%, were obtained with the Pt/CeO2 and Pt/Fe2O3 catalysts in the 100-400°C range. For the Pt/La0.7Sr0.2Ce0.1FeO3 catalyst, addition of 5% H2O in the feed stream at 140°C resulted in a widening of the operating temperature window with appreciable NO conversion and no negative effect on the stability of the catalyst during 20 h on stream. In addition, a remarkable N2 yield (93%) after 20 h on 0.25% NO/1% H2/5% O2/5% H2O/He gas stream at 140°C has been observed. Remarkable N2 selectivity values in the range of 80-90% have also been observed in the 100-200°C low-temperature range either in the absence or in the presence of water in the feed stream. A maximum specific integral reaction rate of 443.5 μmol N2/s·g of Pt metal was measured at 160°C during reaction with a 0.25% NO/1% H2/5% O2/5% H2O/He gas mixture. This value is higher by 90% than the corresponding one observed on the 0.1 wt% Pt/SiO2 catalyst at 120°C and it is the highest value ever reported for the reaction at hand in the 100-200°C low-temperature range on Pt-based catalysts. A TOF value of 13.4 × 10-2 s-1 for N2 formation was calculated at 110°C for the Pt/La0.7Sr0.2Ce0.1FeO3 catalyst. Temperature-programmed desorption (TPD) of NO and transient titration experiments of the catalyst surface following NO/H2/O2 reaction have revealed important information concerning the amount and chemical composition of active and inactive (spectator) adsorbed N-containing species present under reaction conditions.
Keywords: Catalysts; Low temperatures